MEMILIH PEMIMPIN NON MUSLIM DALAM AL-QUR`AN - Jaka Ghianovan, Jaka Ghianovan; Nidhom, Khoirun; Jamil, Ahmad; Abadi Siregar, Mahfuzo (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2020)
Regions and countries with Muslim majority populations have not fully accepted leaders who are not from within their circles. This case has occurred in several countries, one of which is Indonesia, such as the appointment of the Lenteng Agung village chief, Susan Jasmine Zulkifli, who is a Christian. In addition, there was also the appointment of Basuki Tjahaja Purnama as the Governor of DKI Jakarta who had a Christian and Chinese background. The above case makes the need for research from the point of view of al-Qur`an through Hamka's Tafsir al-Azhar and M. Quraish Shihab's Tafsir al-Mishbah by proposing formulas, namely: 1) How to interpret the verses choosing a non-Muslim leader in the Koran according to Hamka and Muhammad Quraish Shihab? 2) How are the similarities and differences between Hamka's interpretation and Muhammad Quraish Shihab regarding the verses of the Koran about choosing a non-Muslim leader in the Qur'an? This research is a library research (Library Research) with the thematic method or Mawd u> 'i> as well as a comparison of the two interpretations. The conclusion of this research is that Hamka refuses to make non-Muslims as leaders, while M. Quraish Shihab does not directly prohibit choosing non-Muslims as leaders. The common ground between Hamka and M. Quraish Shihab is that they both prohibit choosing non-Muslim leaders. The difference is that Hamka understands based on the birth of the text, while M. Quraish Shihab is based on context.",